Enhanced proliferation in a prawn embryonic primary cell culture ectopically expressing mutated Ras - Sudarshan, Gurucharan; Weil, Simy; Rotem-Dai, Noa; Manor, Rivka; Greenshpan, Yariv; Goldstein, Oron; Sharabi, Omri; Aflalo, Eliahu D.; Ofir, Rivka; Rosental, Benyamin; Gazit, Roi; Sagi, Amir (Frontiers in Marine Science, 2023)
Crustacean cell line immortalization has gained a great deal of attention in recent decades for both scientific and applied reasons. Our goal in this study was to advance the state of art towards establishing an immortalized cell line by improving the proliferation rates of primary cells isolated from embryos of the giant freshwater prawn Macrobrachium rosenbergii by using a lentivirus expressing the Ras oncogene. The choice of Ras derived from its involvement in various cellular pathways, such as cell growth, differentiation, and survival, and its use as a tool for in-vitro immortalization, e.g., a specific mutated Ras (RasV12) was used to generate an arthropod cell line. Complementarily, in-silico screening of M. rosenbergii transcriptomic libraries for Ras expression indicated that Ras is already expressed at very early stages of embryo development. In the current study, we transduced primary M. rosenbergii embryonic cells with a lentivirus expressing RasV12 by using the white spot syndrome virus (WSSV IE1) promoter. Expression and sequencing (as followed by sequencing cDNA, confocal microscopy and FACS analysis) of the mutated Ras in the transduced cells confirmed that the lentivirus was successfully integrated into the genome. The lenti-MrRas transduction rate was 23% in the total primary cell population and more than 80% in a sub-population of cells with high granularity. Proliferation of lenti-MrRas transfected cells was enhanced to almost 1200% of the seeding density by the end of our experiment (18 days), which was double that of the control. We were thus successful in enhancing the longevity of embryonic primary cell cultures by ectopic expression of the mutated Ras protein, but the improvement was not sufficient for immortalization.